Large Tailings Disposal — Conventional Versus Paste - Rayo, J; Fuentes, R; Orellana, R (Paste 2009: Proceedings of the Twelfth International Seminar on Paste and Thickened Tailings, 2009)
The use of paste technology has been unexplored in the case of large tailing disposal systems. Despite the challenges it faces for large slurry flows, the benefits of water recovery could make this technology very attractive for future tailings disposal projects. This paper presents an economic and strategic comparison between the use of the paste technology and the conventional tailings dams system. Both alternatives are designed for the disposal of 30 years of production of a real plant, considering a processing capacity of more than 100,000 dry tonnes per day.